A Heart Failure-Associated SCN5A Splice Variant Leads to a Reduction in Sodium Current Through Coupled-Gating With the Wild-Type Channel - Zheng, Yang; Wan, Xiaoping; Yang, Dandan; Ramirez-Navarro, Angelina; Liu, Haiyan; Fu, Ji-Dong; Deschênes, Isabelle (Frontiers in Physiology, 2021)
Nav1.5, encoded by the gene SCN5A, is the predominant voltage-gated sodium channel expressed in the heart. It initiates the cardiac action potential and thus is crucial for normal heart rhythm and function. Dysfunctions in Nav1.5 have been involved in multiple congenital or acquired cardiac pathological conditions such as Brugada syndrome (BrS), Long QT Syndrome Type 3, and heart failure (HF), all of which can lead to sudden cardiac death (SCD) – one of the leading causes of death worldwide. Our lab has previously reported that Nav1.5 forms dimer channels with coupled gating. We also found that Nav1.5 BrS mutants can exert a dominant-negative (DN) effect and impair the function of wildtype (WT) channels through coupled-gating with the WT. It was previously reported that reduction in cardiac sodium currents (INa), observed in HF, could be due to the increased expression of an SCN5A splice variant - E28D, which results in a truncated sodium channel (Nav1.5-G1642X). In this study, we hypothesized that this SCN5A splice variant leads to INa reduction in HF through biophysical coupling with the WT. We showed that Nav1.5-G1642X is a non-functional channel but can interact with the WT, resulting in a DN effect on the WT channel. We found that both WT and the truncated channel Nav1.5-G1642X traffic at the cell surface, suggesting biophysical coupling. Indeed, we found that the DN effect can be abolished by difopein, an inhibitor of the biophysical coupling. Interestingly, the sodium channel polymorphism H558R, which has beneficial effect in HF patients, could also block the DN effect. In summary, the HF-associated splice variant Nav1.5-G1642X suppresses sodium currents in heart failure patients through a mechanism involving coupled-gating with the wildtype sodium channel.